Design and development of a spatial mixed reality touring guide to the Egyptian museum - Hammady, Ramy; Ma, Minhua; Strathern, Carl; Mohamad, Mostafa (Multimedia tools and applications, 2020)
Many public services and entertainment industries utilise Mixed Reality (MR) devices to develop highly immersive and interactive applications. However, recent advancements in MR processing has prompted the tourist and events industry to invest and develop commercial applications. The museum environment provides an accessible platform for MR guidance systems by taking advantage of the ergonomic freedom of spatial holographical Head-mounted Displays (HMD). The application of MR systems in museums can enhance the typical visitor experience by amalgamating historical interactive visualisations simultaneously with related physical artefacts and displays. Current approaches in MR guidance research primarily focus on visitor engagement with specific content. This paper describes the design and development of a novel museum guidance system based on the immersion and presence theory . This approach examines the influence of interactivity, spatial mobility, and perceptual awareness of individuals within MR environments. The developmental framework of a prototype MR tour guide program named MuseumEye incorporates the sociological needs, behavioural patterns, and accessibility of the user. This study aims to create an alternative tour guidance system to enhance customer experience and reduce the number of human tour guides in museums. The data gathering procedure examines the functionality of the MuseumEye application in conjunction with pre-existing pharaonic exhibits in a museum environment. This methodology includes a qualitative questionnaire sampling 102 random visitors to the Egyptian Museum in Cairo. Results of this research study indicate a high rate of positive responses to the MR tour guide system, and the functionality of AR HMD in a museum environment. This outcome reinforces the suitability of the touring system to increase visitor experience in museums, galleries and cultural heritage sites.